Rab35-regulated lipid turnover by myotubularins represses mTORC1 activity and controls myelin growth - Linda Sawade (Nature Portfolio, 2020)
Charcot-Marie-Tooth (CMT) is an inherited peripheral neuropathy. Here, the authors show that Rab35 forms a complex with genes implicated in CMT, MTMR13 and MTMR2, which regulates myelin growth by controlling mTORC1 signaling through lipid turnover.